Features of the Functioning of a Foreign Transnational Bank in Russia - Liangliang Ren; Vladimir Grigoriev (Communications of International Proceedings, 2022)
The inflow of foreign capital is an important factor in the development of the country's banking sector, due to the fact that foreign capital provides access to the Russian banking market with modern technologies, new financial products, contributes to an increase in the culture of corporate governance in credit institutions, the development of competition between credit institutions and the improvement of modern banking. As China's economy grows rapidly, so does their banking sector. It is growing all over the world, aiming to take the first place in the global economy. Chinese banks are growing significantly both domestically and internationally - no wonder they make up the largest global banking sector in the world. As we all know, China has the largest number of export goods, so it has established many banks to facilitate money transfers to China. As of 2022, there are over 4,436 different banking institutions in China domestically. In the markets of foreign countries, Chinese financial institutions will have to compete both with the structures operating in this market and with financial companies in Western countries. Therefore, it is necessary to assess the prospective trends in the development of international operations of banks in leading countries. All of the above determines the relevance of the study of the current positions of Chinese financial companies in the foreign market.
Keywords: foreign banks; banking market; banking system; financial structure; foreign investment.